2011
DOI: 10.20965/ijat.2011.p0773
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Static and Dynamic Characteristics of Water Hydrostatic Porous Thrust Bearings

Abstract: A moving table supported by aerostatic bearings can achieve excellent accuracy of motion because of its noncontact support and, hence, it is used in various precision machine tools and measuring equipment. However, because of low viscosity of air, the damping coefficient of aerostatic bearings is not very high, causing vibration with nanometer-order amplitudes. The accuracy of machine tools and measuring equipment could deteriorate because of this vibration. It is expected that water hydrostatic bearings would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Hydrostatic porous bearings can be easily constructed because the porous material becomes a viscous restrictor itself. It was consequently found that water hydrostatic porous thrust bearings have higher maximum load capacity and slightly lower stiffness than water bearings with a capillary restrictor [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrostatic porous bearings can be easily constructed because the porous material becomes a viscous restrictor itself. It was consequently found that water hydrostatic porous thrust bearings have higher maximum load capacity and slightly lower stiffness than water bearings with a capillary restrictor [5].…”
Section: Introductionmentioning
confidence: 99%
“…As for hydrostatic water bearings, a constant-flow type is more suitable than a constant-pressure type. Nishitani et al 5 investigated the static and dynamic characteristics of water hydrostatic thrust bearings using porous material and compared it with conventional pocket hydrostatic bearings with a capillary restrictor. Hydrostatic porous bearings can be easily constructed because the porous material can develop into a viscous restrictor itself.…”
mentioning
confidence: 99%